MEDICAL BIOTECHNOLOGY: THE INDIAN SCENARIO - Sarojini, Suma (Asian Horizons, 2013)
Medicines are indeed a boon for the suffering living being, be it an animal or a human being. From time immemorial man has been on the lookout for medicines to relieve pain and suffering. The field of Biotechnology has provided solutions to many health care problems. If at all Biotechnology has revolutionized any sector, we could tell without doubt that it is the medical field. Indian Biotech companies are not far behind in contributing to the world of medicine. In fact, the Bangalore based company, BIOCON is listed one among the top 10 Biotech companies of the world.